Strategy for increasing the market share of Islamic Banks in Indonesia through Third-party fundraising and financing - Rahima Kumala; Nurhayati Nurhayati; Muhammad Yafiz (Universitas Negeri Surabaya, 2025)
This research aims to formulate strategies to increase the market share of Islamic banks in Indonesia through the optimization of Third Party Funds (DPK) and financing, which are the main internal factors supporting the growth of Islamic banking. Based on the background, the low market share of Islamic banks is caused by several main issues, such as limited technology, low product innovation, lack of Islamic financial literacy, and suboptimal data protection. This research uses the Analytic Network Process (ANP) method, which involves expert respondents from regulators, academics, practitioners, and the community. Data collection was conducted through in-depth interviews, questionnaires, and analysis using Super Decision software. The research results indicate that priority solutions to increase market share include technological updates, enhanced literacy through education and collaboration between institutions, as well as synergy among stakeholders. The main strategies proposed include strengthening synergy and collaboration, enhancing technological innovation, and expanding sharia financial literacy. This research makes a significant contribution in identifying problems, solutions, and relevant strategies to support the development of Islamic banking in Indonesia. The results are expected to serve as a reference for regulators, Islamic banking, academics, and the community in promoting the sustainable growth of the Islamic finance industry.